Samuel Kimball, Charter, Other Powers, and Ordinances of the City of Lawrence 149 (1866) - (:unkn) unknown (My University, 1863)
§ 10: Prohibited the concealed carry of any pistol, Bowie-knife, or other deadly weapon. Violators fined not less than one nor more than ten dollars.
Keywords: CARRY - CONCEALED